Optimizing Energy Efficiency: Case Study of a Steel and Iron Distributor Building - Fina Zaimah Maznah; Fadlli Ash Shidiqqy; Wisnu Indrawan; Dimas Adiwijaya (Jurnal Ilmu Multidisiplin, 2025)
The swiftly growing demand for electricity in Indonesia, expected to increase substantially by 2025, requires the adoption of efficient energy conservation measures within the commercial sector. This study offers a thorough electrical energy audit of a Steel and Iron Distributor Building situated in West Java, with the objective of assessing actual energy performance and identifying Energy Conservation Opportunities (ECOs). The research methodology adheres to a comprehensive audit framework, employing secondary data from 2024 electricity invoices and primary data obtained through on-site field measurements conducted in October 2023 to analyses load profiles and consumption patterns. The principal metric employed for evaluation was Energy Consumption Intensity (ECI). The analysis indicated that the building's ECI, calculated from historical data, was 54.26 kWh/m²/year, whereas the value obtained from comprehensive load estimation was 65.54 kWh/m²/year. Both figures are considerably lower than the standard benchmark of 180.95 kWh/m²/year set by the Agency for the Assessment and Application of Technology (BPPT) for office buildings. Consequently, the facility is designated as "Very Efficient" in accordance with Minister of Energy and Mineral Resources Regulation No. 13 of 2012. Despite this high-performance rating, the audit suggests targeted enhancements to promote sustainability, such as a full transition to LED technology, the implementation of rigorous preventive maintenance protocols for air conditioning units, and the deployment of real-time energy monitoring systems to observe future consumption patterns.